Executive Function In Early Childhood: What Do Teachers Know And Do In The Classroom? - Ifana, Fitra; Rahmawati, Yuli; Supena, Asep (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study is to investigate how early childhood education (ECE) teachers comprehend and use learning techniques that promote the development of executive function in young children. The three primary components of executive functions—working memory, inhibitory control, and cognitive flexibility—are essential to children's self-regulation and preparation for learning. Several early childhood education teachers in the Jakarta and Bekasi regions were interviewed in-depth to gather data using a qualitative methodology. The research findings indicate that most teachers are not familiar with the term "executive function," but in practice, they have been conducting activities that support these aspects in daily learning. Nevertheless, the implementation of these activities has not been fully directed or recognized as part of executive function development. Therefore, efforts to enhance teacher professionalism through specialized training or seminars are needed so that their understanding and pedagogical practices can be more optimal in supporting the development of executive functions in early childhood.